Predicting community participation after spinal cord injury in Thailand - Jatuporn Suttiwong (2018)
© 2015 The Authors. Objective: To identify the predictors of community participation after spinal cord injury. Design: Cross-sectional design. Methods: A total of 139 persons with spinal cord injury living in the community completed 4 instruments: the Impact on Participation and Autonomy (IPA-Thai version), the Craig Hospital Inventory of Environmental Factors (CHIEF-SF-Thai version), the Personal Resource Questionnaire (PRQ2000-Thai version), and a personal history questionnaire. Functional performance was assessed using the Functional Independence Measure (FIM) motor subscale. Results: Participants comprised 79% males. Fifty-one percent of variance in community participation was explained by social support, functional performance, age, and age at time of injury. Conclusion: Key predictors of community participation were the availability of social support and the individual's functional performance. These predictors should be emphasized when developing interventions in rehabilitation and community settings.